High holidays on the high seas: the voyage experience of Jewish migrants sailing to Australia in the mid-nineteenth century. Issue 4 (2nd October 2019) - Offer, Elizabeth
ABSTRACT: For emigrants who undertook the long and treacherous voyage to Australia's distant shores in the mid-nineteenth century, their faith sailed with them. While voyages of Jewish migrants have often been described as a 'secularising' experience, this article offers a new perspective, based on unpublished archival sources. The religious practices of Jewish emigrants continued on-board ships as well as in their later lives in the colonies. Ship voyages for Jewish passengers sailing to Australia entailed contact with Christianity and at times conflict with Gentile emigrants, producing voyages which were anything but secular.